2020
DOI: 10.3390/nu12051519
|View full text |Cite
|
Sign up to set email alerts
|

A Dose-Dependent Effect of Carnipure® Tartrate Supplementation on Endurance Capacity, Recovery, and Body Composition in an Exercise Rat Model

Abstract: The objective of this work is to investigate the effects of Carnipure® Tartrate (CT) supplementation with or without exercise on endurance capacity, recovery, and fatigue by assessing time to exhaustion as well as body weight and composition in rats. In addition, antioxidant capacity has been evaluated by measuring malondialdehyde (MDA) levels and antioxidant enzyme (superoxide dismutase, SOD; catalase, CAT; glutathioneperoxidase; GSHPx) activities. Fifty-six male Wistar rats were divided into eight groups inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 70 publications
1
4
0
Order By: Relevance
“…The current trial showed that muscle damage after exercise was lowered by L-carnitine tartrate supplementation, most likely by lowering ROS, as evidenced by an increase in serum SOD, a major cellular antioxidant enzyme. Previous research indicated that 6 weeks of L-carnitine tartrate supplementation increased serum SOD levels, improving the antioxidant status in an animal model [7]. Therefore, we hypothesized and confirmed, in the present trial, that L-carnitine tartrate supplementation for 5 weeks also increased serum SOD levels in both males and females, as well as across age groups.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current trial showed that muscle damage after exercise was lowered by L-carnitine tartrate supplementation, most likely by lowering ROS, as evidenced by an increase in serum SOD, a major cellular antioxidant enzyme. Previous research indicated that 6 weeks of L-carnitine tartrate supplementation increased serum SOD levels, improving the antioxidant status in an animal model [7]. Therefore, we hypothesized and confirmed, in the present trial, that L-carnitine tartrate supplementation for 5 weeks also increased serum SOD levels in both males and females, as well as across age groups.…”
Section: Discussionsupporting
confidence: 85%
“…L-carnitine is primarily stored in skeletal and cardiac muscles because of their high mitochondrial density and high energy demand [4]. Because of L-carnitine's role in the energy-generating processes, it was shown to be an important player in muscular performance, development, recovery, and physical exercise [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Rodents subjected to a high level training exercise (which serves as an inflammatory stimulus) were supplemented with different doses of L-carnitine by oral gavage for a period of 6 weeks as previously described [ 28 ]. The L-carnitine doses used 25, 50, 100, 200 and 400 mg/kg correspond to human doses of 250, 500, 1000, 2000 and 4000 mg per day, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The L-carnitine’s physiological role is to transport fatty acid through the cellular and mitochondrial membranes leading to their usage as a source of energy by the Krebs cycle in the mitochondria [ 21 ]. This enhanced mitochondrial activity was indicated by a decrease in the lactate levels in the rodent serum [ 28 ]. It has been recently reported that L-carnitine can physically bind the nuclear receptor HNF4-α and increase its levels [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation